Combined Deletion of Slc30a7 and Slc30a8 Unmasks a Critical Role for ZnT8 in Glucose-Stimulated Insulin Secretion - Syring, Kristen E. (Endocrinology, 2016)
Polymorphisms in the SLC30A8 gene, which encodes the ZnT8 zinc transporter, are associated with altered susceptibility to type 2 diabetes (T2D), and SLC30A8 haploinsufficiency is protective against the development of T2D in obese humans. SLC30A8 is predominantly expressed in pancreatic islet β-cells, but surprisingly, multiple knockout mouse studies have shown little effect of Slc30a8 deletion on glucose tolerance or glucose-stimulated insulin secretion (GSIS). Multiple other Slc30a isoforms are expressed at low levels in pancreatic islets. We hypothesized that functional compensation by the Slc30a7 isoform, which encodes ZnT7, limits the impact of Slc30a8 deletion on islet function. We therefore analyzed the effect of Slc30a7 deletion alone or in combination with Slc30a8 on in vivo glucose metabolism and GSIS in isolated islets. Deletion of Slc30a7 alone had complex effects in vivo, impairing glucose tolerance and reducing the glucose-stimulated increase in plasma insulin levels, hepatic glycogen levels, and pancreatic insulin content. Slc30a7 deletion also affected islet morphology and increased the ratio of islet α- to β-cells. However, deletion of Slc30a7 alone had no effect on GSIS in isolated islets, whereas combined deletion of Slc30a7 and Slc30a8 abolished GSIS. These data demonstrate that the function of ZnT8 in islets can be unmasked by removal of ZnT7 and imply that ZnT8 may affect T2D susceptibility through actions in other tissues where it is expressed at low levels rather than through effects on pancreatic islet function.